PENGARUH PENDEKATAN STEM TERHADAP MINAT DAN HASIL BELAJAR BIOLOGI SISWA : STUDI KASUS KUANTITATIF DI SMAN 3 PALANGKA RAYA - Dina Pratika Lestari; Mutia Harimatul Hasanah; Yatin Mulyono (Jurnal Metabio, 2025)
This study aims to analyze the influence of the Science, Technology, Engineering, and Mathematics (STEM) approach on increasing interest and learning outcomes of Biology in students of SMAN 3 Palangka Raya. The method used was a meta-analysis by examining seven relevant articles and meeting the inclusion criteria, such as experimental or quasi-experimental quantitative design, middle-level student subjects, and quantitative data that included pretest scores, posttest, standard deviation, and sample count. The results showed that the application of the STEM approach consistently increased students' interest and learning outcomes, with an average difference in pretest and posttest scores of 17.8 points. These findings reinforce the argument that STEM approaches are effective in encouraging student engagement, improving conceptual understanding, and developing critical and collaborative thinking skills in science learning. This study recommends the systematic integration of STEM in curriculum and teacher training to support the quality of learning in secondary schools.